The speech of modern motherhood and the construction of femininity through the press. Central and southern Buenos Aires in the late nineteenth and early twentieth centuries (Quinto Sol, 2011)
At the end of the nineteenth century, a process of modernization and development took place in Argentina, within the frame of the nationstate consolidation. In this context, the country witnessed a discursive profusion that expected to introduce disciplinary instruments into society, among which the creation of a modern maternal ideal can be mentioned. This paper analyzes the main topics of such discourses, through one the main media available to spread them in rural central and southern Buenos Aires in our period: the local press.
Keywords: maternity; ideal; press; speeches